Bear in love - Pinkwater, Daniel Manus, 1941- (Candlewick Press, 2012)
A bear with a secret admirer who leaves sweet, crunchy treats outside his cave each night tries to repay the kindness with honey, but comes to find out that his new friend is smaller, cuter, and fonder of carrots than any bear.